Penerapan Audit Berbasis Artificial Intelligence di Indonesia: Sebuah Metasintetis - Ramadhan Mukhtar, Multazam; Andi Muhammad Syahrul; Ahmad Habibi (Journal of Economic Education and Entrepreneurship Studies, 2023)
This research aims to find out how the application of advanced artificial intelligence technology in conducting audits in Indonesia. The method used by the analysis tool is a metasynthesis of a number of qualitative studies on AI-based auditing. The results of this study provide new insights into the barriers, conveniences, challenges, and opportunities in the application of AI-based auditing in Indonesia. Auditors face barriers to implementing AI technology, which involves adjusting their skills and experience. Challenges in implementing AI-based auditing include technical aspects, skills, ethics, and data security. Implementing AI-based auditing brings a number of conveniences in improving audit efficiency, accuracy, and quality. The opportunities in implementing AI-based auditing are immense and can provide a number of significant benefits to the auditing and accounting profession as a whole.